Campos laborales que se desprenden de las festividades religiosas populares de la ciudad de Riobamba durante los años 2022 -2023. - Obregón Pérez, Jorge Enrique (2024)
The main objective of this research is the analysis of the labor fields that arise from the popular religious festivals in the city of Riobamba, which produce a direct economic livelihood within households and families of both formal and informal trade. During the research project, a mixed approach was used, where the information collected was obtained through the use of interviews and surveys to obtain the opinion of the protagonists of the subject. On the other hand, the description of the popular religious festivities was made through the bibliographic compilation of media and authors of the city. The interview and survey tools used, facilitated obtaining the analysis of the people who relate their daily experiences through their work, as well as the resilience despite adversities, knowing firsthand the importance of devotion to religion in this city and how the resilience of the different workers is reflected in their words of effort and daily struggle. In conclusion, the riobambeña society is eminently religious and the popular religious festivities promote models of commerce where different places and labor fields arise that have been maintained through time, after the pandemic the resilience of the society is propelled by motivations within the home and they have adapted their work to the different digital strategies of modernity.